PKS & kembaranya bergiat jadi demokrat di Indonesia, Mesir & Turki / Anthony Bubalo, Greg Fealy, dan Whit Mason; Penerjemah, Syamsul Rijal - BUBALO, Anthony; FEALY, Greg; MASON, Whit; SYAMSUL Rijal (Komunitas Bambu, 2012)
xiv, 122 hlm. ; 21 cm.